Parate Execution Agianst Third Party Interest From Debtor Default and Creditor Breach Within The Framework Of National Security Law - Pranowo, Yusuf; Yuhelson , Yuhelson; Akkapin, Supaphorn (CV. Era Digital Nusantara, 2024)
This research aims to analyse the implementation of parate execution in the legal system of property security in Indonesia, especially in relation to the protection of third-party rights. Although parate execution is a creditor's right that is legally regulated in legislation, its practice often raises issues of justice, legal certainty, and legal expediency. Third parties, such as heirs or auction buyers, often suffer losses because their rights are not properly considered or protected. This research uses a normative juridical approach by analysing parate execution cases involving conflicts between creditors, debtors, and third parties. The results show that there is injustice in the implementation of parate execution when the rights of third parties are ignored, as well as legal uncertainty due to inconsistent procedures and rules for execution. In addition, the current legal system has not been able to create optimal legal benefits, as third parties often do not receive adequate protection. Based on these findings, the study recommends clearer regulatory reforms and transparent procedures to protect the rights of third parties. This reform is needed to ensure that the implementation of parate execution is fair, provides legal certainty, and produces equitable benefits for all parties involved.